GJB6-D13S1830 and GJB6-D13S1854 Deletions in Patients with non-Syndromic Prelingual Deafness - Mercedes Arceo Álvarez; Estela Morales Peralta; Yuledmi Perdomo Chacón; Teresa Collazo Mesa (Revista Finlay)
Foundation: GJB6-D13S1830 and GJB6-D13S1854 deletions are pathogenic variants of the GJB6 gene, which has been shown to be the second cause of autosomal recessive non-syndromic deafness in Spain, where some of our ancestors come from. These deletions have been found associated with pathogenic variants of the GJB2 gene in individuals with hearing loss. Objective: to describe the presence of GJB6-D13S1830 and GJB6-D13S1854 deletions in patients with autosomal recessive non-syndromic deafness. Method: a descriptive cross-sectional study was carried out on 433 patients registered with autosomal recessive non-syndromic deafness at the National Center for Medical Genetics, in whom the presence of the pathogenic variant c.35delG of the GJB2 gene had previously been ruled out. homozygosity. The multiplex polymerase chain reaction technique was applied, by which the genotype was described and its frequency was determined. Results: deletions of the GJB6 gene were identified in 13 individuals, 12 in heterozygosity - in seven of them GJB6-D13S1830 and in five GJB6-D13S1854 - and one with the deletion GJB6-D13S1830 in homozygosity. The pathogenic variant c.35delG of the GJB2 gene had previously been identified in heterozygosity in three of the patients in whom GJB6-D13S1830 was identified and two in whom GJB6-D13S1854 was observed. Conclusion: GJB6-D13S1830 and GJB6-D13S1854 deletions appeared in a low proportion of the patients with autosomal recessive non-syndromic deafness studied and were mainly identified in heterozygosity.